2014
DOI: 10.1007/s12663-014-0717-6
|View full text |Cite
|
Sign up to set email alerts
|

Giant Osteoma of Mandible Causing Dyspnea: A Rare Case Presentation and Review of the Literature

Abstract: Osteomas are benign slow growing tumors of bone. Tumors are usually asymptomatic until they attain remarkable size and cause asymmetry or dysfunction. In view of few reported cases of giant osteoma of mandible, this article presents a case of giant osteoma of left mandible in a 53-year old male causing dyspnea due to compression of air way space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Difficulty in mastication, swallowing, and breathing secondary to large osteomas has also been reported (2,25,26). In the case report of Sadeghi et al (27) a giant PO (9.5×8 cm) caused dyspnea. Similar to the majority of published cases in the literature, any symptoms accompanying to the facial asymmetry were not detected in our case.…”
Section: Discussionmentioning
confidence: 94%
“…Difficulty in mastication, swallowing, and breathing secondary to large osteomas has also been reported (2,25,26). In the case report of Sadeghi et al (27) a giant PO (9.5×8 cm) caused dyspnea. Similar to the majority of published cases in the literature, any symptoms accompanying to the facial asymmetry were not detected in our case.…”
Section: Discussionmentioning
confidence: 94%
“…Tarsitano and Marchetti7 reported a case of mandibular osteoma associated with obstructive sleep apnoea syndrome; Sadeghi et al 8 reported a case of giant osteoma presenting as dyspnoea.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoma is reported in the non-osteoid organs such as the stomach ( Woo et al , 2019 ), skin (osteoma cutis) ( Fernandez et al , 2012 ), and tongue (lingual osteoma) ( Goldschmidt and Thrall, 1985 ). The most significant region of the osteoma tumor is the maxillofacial bones, such as the mandible, maxillae, and nasal/frontal bone, and maxillofacial bones are more susceptible to osteoma formation ( Ogbureke et al , 2007 ; Sadeghi et al , 2015 ; Khandelwal et al , 2016 ). The purpose of this study is to describe the mandibular osteoma in a 5-year-old dog undergoing a surgical procedure to remove this tumor by mandibulectomy.…”
Section: Introductionmentioning
confidence: 99%